HUBUNGAN PERSEPSI MAHASISWA PADA KINERJA DOSEN TERHADAP TINGKAT KELULUSAN MAHASISWA - Asri, Yoana Nurul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2018)
Based on the low pass rate then made a research about the relationship of perceptions of lecturer performance with graduation rate of engineering students at the Nurtanio University. The sampling technique used is simple random sampling with the number of samples taken at random as many as 60 students who take physics courses. Obtained average results From the above statistical results seen as 92% of students agree that the lecturer already has a good readiness to teach. As many as 85% of students stated that lecturers already have material readiness. As many as 88% stated that the lecturer has discipline in teaching. For the category of evaluation of teaching as much as 83% of students stated that the lecturers have fulfilled. As many as 97% stated that the personality of lecturers in teaching in the classroom and personality outside the class is good. It's just for the correlation between courses with courses has lowest score as much as 68% said there was a positive correlation. Based on the result of pearson product moment test, the correlation between student's perception on lecturer performance has an effect on graduation rate of student with value equal to 0,625 in enough category.